Avanço maxilomandibular e glossectomia da linha média no tratamento da síndrome da apnéia hipopnéia obstrutiva do sono moderada e severa - Colombini, Nelson Eduardo Paris (2010)
Introduction: To describe the results obtained by the Maxillo Mandibular Advancement (MMA), associated to a glossectomy of Medium Line (GML) to CO2 Laser in the surgical treatment of Obstructive Sleep Apnea-Hypoapnea Syndrome (ASOSH), from moderate to severe, with adequate analysis of macroscstruture e microstructure of the sleep. Casuistics and Method: In the period from February 2005 to December 2008, 22 sequencial patients with ASOSH, from moderate to severe, with or without maxillary mandibular bone alterations, were selected. These patients were submitted to MMP plus GML using a CO2 laser. All patients underwent clinical, polissonographic and cephalometric evaluations. The polissonographic parameters used were: IAH, MD, Minimum SAT O2% < measured in minutes, sleep stages N1, N2, N3 and REM, preoperative and postoperative. The cephalometric parameters used were: SNA, SNB, PAS, PP2 – PP2, preoperative and postoperative. Results: Evaluation of eventual differences in the preoperative and postoperative moments were investigated with the appropriate statistical tools. The surgical treatment proved to be effective in 8, out of 22 of the cases (36.36%), according to international criteria of normality. On the other hand, in these patients the IAH was not the best parameter to evaluate the therapeutic success. The MD (68.18% of improvement), stage N3 (59.09% of improvement) and Minimum SAT O2% < 90 measured in minutes (81.81% of improvement) demonstrated that they were the best instruments for characterizing the laboratorial control of the disease. Discussion: The MMA has expanded the dimensions of the pharynx and the hypopharynx. The GLM was associated in order to maximize the VAS, improve the stability of the dental occlusion, as well as the function of the temporomandibular joint, reducing the morbidity of the procedure. A postoperative evaluation with polysomnography showed improvements of the parameters in both macro and microarchitecture of the sleep (in relation to preoperative findings), besides proving that the IAH is not the best parameter for a postoperative evaluation (this applies to the patients of this series). Conclusions: The surgical treatment performed with MMA, associated to the GLM with CO2 laser was effective to treat patients with from ASOSH : - The improvement using the most accepted parameter by the international community (IAH < 5/ hour) was 8 out of the 22 (36.36%); - The IAH was not the best instrument to evaluate the control of the disease; - Were MD, stage N3 and Minimum SAT O2% < 90 measured in minutes showed that they are good indicators of the control of the disease (postoperative moment); - The Minimum SAT O2% < 90 measured in minutes was the best parameter in the evaluation of the surgical treatment (18/22 or 81.81%).